The effect of antigen encapsulation in chitosan particles on uptake, activation and presentation by antigen presenting cells - Koppolu, Bhanu prasanth (2012)
Particle-based vaccine delivery systems are under exploration to enhance antigen-specific immunity against safe but poorly immunogenic polypeptide antigens. Chitosan is a promising biomaterial for antigen encapsulation and delivery due to its ability to form nano- and microparticles in mild aqueous conditions thus preserving the antigenicity of loaded polypeptides. In this study, the influence of chitosan encapsulation on antigen uptake, activation and presentation by antigen presenting cells (APCs) is explored. Fluorescein isothiocyanate-labeled bovine serum albumin (FITC-BSA) and ovalbumin (OVA) were used as model protein antigens and encapsulated in chitosan particles via precipitation-coacervation at loading efficiencies >89%. Formulation conditions were manipulated to create antigen-encapsulated chitosan particles (AgCPs) with discrete nominal sizes (300nm, 1µm, and 3µm). Uptake of AgCPs by dendritic cells and macrophages was found to be dependent on particle size, antigen concentration and exposure time. Flow cytometry analysis revealed that uptake of AgCPs enhanced upregulation of surface activation markers on APCs and increased the release of pro-inflammatory cytokines. Lastly, antigen-specific T cells exhibited higher proliferative responses when stimulated with APCs activated with AgCPs versus soluble antigen. These data suggest that encapsulation of antigens in chitosan particles enhances uptake, activation and presentation by APCs.